2002
DOI: 10.1002/ptr.798
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activity of acylated iridoid glycosides from Scrophularia nodosa

Abstract: Three acylated iridoid glycosides (E)-6-O-(2", 4"-diacetyl-3" -O-p-methoxycinnamoyl)-alpha-L-rhamnopyranosyl catalpol (scopolioside A) (1), (E)-6-O-(2"-acetyl-3", 4"-di-O,O-p-methoxycinnamoyl)-alpha-L-rhamnopyranosyl catalpol (scrophuloside A(4)) (2) and (E)-6-O-(2",3"-diacetyl-4"-O-p-methoxycinnamoyl)-alpha-L-rhamnopyranosyl catalpol (scrovalentinoside) (3) have been isolated from the dried seed pods of Scrophularia nodosa by HPLC. Their structures were determined by 1D and 2D NMR, UV/Vis and mass spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 6 publications
0
49
0
Order By: Relevance
“…A wide range of medicinal properties are attributed to Verbascum species (Vijayavitthal et al, 1998;Tuzlaci and Erol, 1999;Konoshima et al, 2000;Sezik et al, 2001;Stevenson et al, 2002;Turker and Camper, 2002;Ahmed et al, 2003;Senatore et al, 2007;Amirnia et al, 2011;Karamian and Ghasemlou, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of medicinal properties are attributed to Verbascum species (Vijayavitthal et al, 1998;Tuzlaci and Erol, 1999;Konoshima et al, 2000;Sezik et al, 2001;Stevenson et al, 2002;Turker and Camper, 2002;Ahmed et al, 2003;Senatore et al, 2007;Amirnia et al, 2011;Karamian and Ghasemlou, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…These differences were also clearly distinct in microscopic histological figures. In addition, by increasing fibroblasts growth, one will prepare the area for excretion of collagen and as a result for faster wound healing (28). The results of the experiments carried out on the above four groups on 7th day of treatment and at the end of treatment showed that the epider-…”
Section: Discussionmentioning
confidence: 98%
“…9, [16][17][18] S. ningpoensis from this family has been used in treatment of upper respiratory disorders, GI difficulties and fever in Chinese medicine. 19 Furthermore, this species was used in restraining ventricular remodeling in order to ameliorate heart failure with subsequent event of MI.…”
Section: Introductionmentioning
confidence: 99%